The Effect of Digital Marketing Learning and TikTok Live Practices on Work Readiness Through Self-Efficacy among Digital Business Students at SMK Labschool UNESA 1 Surabaya - Dwi Maulida; Tri Sudarwanto (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Work readiness among vocational high school (SMK) graduates remains a critical challenge, as reflected in the relatively high unemployment rate among SMK graduates and the persistent mismatch between graduate competencies and the demands of the business and industrial sectors. This condition underscores the need for learning approaches that strengthen students’ technical competencies while enhancing their confidence in entering the workforce. This study aims to analyze the effect of digital marketing learning and TikTok Live practices on work readiness through self-efficacy among Digital Business students at SMK Labschool UNESA 1 Surabaya. A quantitative approach with an explanatory research design was employed. The population comprised 44 eleventh- and twelfth-grade students, all of whom were selected using a total sampling technique. Data were collected through a Likert-scale questionnaire and analyzed using IBM SPSS Statistics 30 through validity testing, reliability testing, classical assumption testing, path analysis, t-tests, coefficient of determination analysis, and the Sobel test. The findings indicate that digital marketing learning and TikTok Live practices have positive and significant effects on both students’ self-efficacy and work readiness. Self-efficacy also has a positive effect on work readiness and partially mediates the effects of digital marketing learning and TikTok Live practices on work readiness. These findings demonstrate that the integration of experience-based digital learning can strengthen students’ competencies, self-confidence, and readiness to enter the workforce. The study contributes to vocational education by highlighting digital marketing learning and TikTok Live practices as relevant instructional strategies for aligning student competencies with contemporary workplace demands.